Effects Euphrates river flow variation in Geographical distribution sand Minerals and path the weathering from AL Baghdadi city to AL Fallujah city - aftan, Laith saadi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Petrographic study Minerals of very fine sand were carried in two terraces of Euphrates river. which starting from AL Baghdadi in the Northwest to- AL Fallujah in the East south. the study were including petrography characterization of light and heavy minerals. The aims of this study to know the ratio of minerals and spatial geographical distribution as well as to explain the effect of the Euphrates river in this distributed and weathering state. The results of this study showed; Convergence ratio of light and heavy minerals in all terraces ancient and modern. The weathering of light minerals increased in the old desert terraces. The heavy minerals (Rutile) showed the pedo stratigraphy between the modern and ancient terraces on the long the path.